Penggunaan Media Interaktif Adobe Flash CS6 pada Pembelajaran Bahasa Indonesia - Herman Wijaya; Hindun Hindun (Jurnal Guru Indonesia, 2023)
The use of interactive learning media is able to create new experiences for students in the learning process. Therefore, the selection of appropriate learning media will have a positive impact on students in the learning process. This study uses the Research and Development (RnD) method to assess the validity and effectiveness of using Adobe Flash CS6 interactive media in learning. The subjects of this research trial were class VII students of MTs Salafiyah Wiradesa, namely 10 students for small-scale trials. 20 experimental class students and 20 control class students on a large-scale test. The results of this study concluded that the use of Adobe Flash CS6 interactive media on procedural text material met the criteria of very feasible to use with a percentage score of 100% by material experts and 96.3% by media experts. The n-gain test result is 0.3508 with moderate criteria. Concluding that interactive media using Adobe Flash CS6 is effectively used and can improve student learning outcomes.Penggunaan media pembelajaran interaktif mampu menciptakan pengalaman baru siswa dalam proses pembelajaran. Sebab itu, pemilihan media pembelajaran yang tepat akan memberikan dampak positif bagi siswa pada proses pembelajaran. Penelitian ini menggunakan metode Research and Development (RnD) untuk menilai validitas dan efektivitas penggunaan media interaktif Adobe Flash CS6 dalam pembelajaran. Subjek uji coba penelitian ini adalah siswa kelas VII MTs Salafiyah Wiradesa yaitu 10 siswa untuk uji coba skala kecil. 20 siswa kelas eksperimen dan 20 siswa kelas kontrol pada uji skala besar. Hasil penelitian ini menyimpulkan bahwa penggunaan media interaktif Adobe Flash CS6 pada materi teks prosedur memenuhi kriteria sangat layak digunakan dengan persentase nilai 100% oleh ahli materi dan 96,3% oleh ahli media. Hasil uji n-gain 0,3508 dengan kriteria sedang. Menyimpulkan media interaktif menggunakan Adobe Flash CS6 efektif digunakan dan dapat meningkatkan hasil belajar siswa.